Finite Element Analysis of Fire Extinguisher for Different Types of Composite Materials - Raed Naeem Hwyyin (Engineering and Technology Journal, 2011)
The stress and strain concentrations of a fire extinguisher made of different types of composite materials are investigated. The prediction of the failure limit and its location in the proposed design is always the associated problem that is inescapable and difficult to be solved completely in the shape design of pressure vessel. A three dimensional analysis in finite element method was made for determining the concentration of stress and strain of the extinguisher. The xtinguisher is made of polyester resin reinforced with different types of fiber glass. The aim of the present investigation is to study the effect of different levels of internal pressure and different types of composite material on the failure limit for limiting capability of applying that product in practical field.The results are compared with those obtained from the corresponding model where xy-strain of composite material reinforced with random fiber glass increases with rate (98%) while in the composite material reinforced with fiber glass arranged with 45o it increases with rate (99.8 %) due to increase in the internal pressure to (0.9-5) MPa. The comparison between theoretical and numerical results gives a good agreement.